Impact Resistance of Laterized Concrete (Journal of Science and Technology, 2016)
Resistance to impact and other suddenly applied loads Is now recognized as one of the significant properties of normal concrete. Result of test on normal concrete have shown that the introduction of steel or fiber reinforcement into the Lenient matrix has a significant effect on the impact resistance of the concrete. The addition of fibre is known to improve many of its properties such at fatigue. toughness. flexural strength and strain capacity. Test are reported on the impact resistance of plain laterized concrete, on fibre-reinforced laterized concrete and the effect of thickness is also investigated. For all three areas investigated the percentage of sand by weight of the total fine aggregate was varied In steps 4 25% up to a maximum 100% corresponding to normal concrete. For the fibre-reinforced laterized concrete the fibre content was varied from 45% M u maximum of 5 percent. For the effect of thickness variation on impact resistance. the thickness of specimen was varied from an initial ark-Ann. of 50Knun and in steps 4 12.72 mm to a maximum thickness of 88.92mm the impact resistance of laterized concrete was found to increase with thickness Ike Impact strength increased with parentage increase in fibre content only at a laterite content of 25 per cent For higher percentages 4 laterite content. the impact resistance does not increase throughout with percentage increase in fibre content Rut there is an optimum value of fibre content above which there was a decrease in Impact strength as fibre content in the cement matrix was increased Ike impact strength of the laterized concrete war also found rare with the laterite content in the cement metric